The Importance of Digital Media in Arabic Language Learning; The Use of Canva in Vocabulary Learning - Ubaidillah Ubaidillah; Muhamad Muflih; Nurul Fajri; Hambali Jaili; Nikmatun Azimah (Jurnal Al-Maqoyis, 2023)
Using media in learning Arabic is an essential way to convey messages and materials quickly to secondary school students. This study explores how students in a modern Islamic boarding school in Indonesia learn Arabic using digital-based media known as Canva, a program that contains both technology and novelty. This research uses mixed methods, with data obtained from observations, interviews, and questionnaires. Results show that learning vocabulary with Canva increases students' motivation and concentration, resulting in more effective and communicative vocabulary learning.